Porosity and Compaction State at the Active Pāpaku Thrust Fault in the Frontal Accretionary Wedge of the North Hikurangi Margin - Jade Dutilleul; S. Bourlange; Y. Géraud (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Characterization of the porosity evolution across the sedimentary section entering subduction zones and accreted sediments provide valuable information for understanding the deformation history at accretionary margins and the physico‐chemical processes in and around fault zones. International Ocean Discovery Program Expeditions 372 and 375 drilled, logged, and cored the reference section on the incoming plate (Site U1520) and across the active Pāpaku thrust (Site U1518), which is a <30° westward‐dipping splay fault in the frontal accretionary wedge at the north Hikurangi margin in a region where tsunami earthquakes and recurrent slow slip events are documented. We observe strong variations of physical properties across the thrust fault. In particular, interstitial porosity increases by ∼10% through the fault zone while it exponentially decreases with depth, showing lower values in the hanging‐wall (HW; on average, ∼36%) than in the footwall (∼42%). Based on comparisons of porosity with the compaction curve at Site U1518 with that of reference Site U1520, we infer an overcompaction in the HW and a nearly normal compaction in the footwall of the Pāpaku thrust. We suggest that the porosity pattern across the thrust infers differences in the maximum burial depth of sediments, characterized by an overcompacted HW that has been uplifted, thrusted, and concomitantly tectonically eroded above the footwall. Porosity data indicate hydrostatic conditions around the thrust fault contrasting with commonly assumed excess pore pressure at the plate interface.